Role of TRPV1 in High Temperature-Induced Mitochondrial Biogenesis in Skeletal Muscle: A Mini Review - Xu, Yixiao; Zhao, Yongcai; Gao, Binghong (Frontiers in Cell and Developmental Biology, 2022)
Transient receptor potential vanilloid 1 (TRPV1) is a protein that is susceptible to cell environment temperature. High temperatures of 40 ℃–45 ℃ can activate the TRPV1 channel. TRPV1 is highly expressed in skeletal muscle and located on the sarcoplasmic reticulum (SR). Therefore, TRPV1 activated by high-temperature stress releases Ca2+ from the SR to the cytoplasm. Cellular Ca2+ accumulation is a key event that enhances TRPV1 activity by directly binding to the N-terminus and C-terminus. Moreover, Ca2+ is the key messenger involved in regulating mitochondrial biogenesis in skeletal muscle. Long-term activation of TRPV1 may promote mitochondrial biogenesis in skeletal muscle through the Ca2+-CaMKII-p38 MAPK-PGC-1α signaling axis. The discovery of the TRPV1 channel highlights the potential mechanism for high- temperature stress improving muscle mitochondrial biogenesis. The appropriate hot stimulus in thermal environments might be beneficial to the muscular mitochondrial adaptation for aerobic capacity. However, the investigation of TRPV1 on mitochondrial biogenesis is at an early stage. Further investigations need to examine the role of TRPV1 in response to mitochondrial biogenesis in skeletal muscle induced by different thermal environments.